Transgresja jako klucz do odczytania literackiego dialogu Egona Bondy’ego i Honzy Krejcarovej - Kijanka, Justyna (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2018)
The article attemp ts to analyse the literary dialogue between two representatives of Czech underground Culture: Egon Bondy and Honza Krejcarová. The authors were inspired by ideas and subjects which were forbidden in the countries of Eastern Europe under communism. Their focus was eroticism and liberated sexuality, mixing kitsch and transcendency, with use of the Bakhtin’s aesthetics of lower stratum of the body. For Bondy and Krejcarová art was a way to find refuge and seek freedom. In my opinion the key to interpret their work is transgression, especially as described in the philosophic work of Georges Bataille. It turns out, that ‘to go beyond’ is for the authors a way to break free from the bonds of socrealistic art. The dialogue held in the so called samizdat, by clandestine copying and distribution, has not lost its scandalous undertone in the course of time.

Artykuł stanowi próbę analizy literackiego dialogu dwojga przedstawicieli czeskiego undergroundu: Egona Bondy’ego i Honzy Krejcarovej. Twórcy ci inspirowali się ideami oraz tematyką zakazaną w krajach Bloku Wschodniego. W centrum zainteresowania stawiali erotyzm oraz wyzwoloną seksualność, mieszając kicz i transcendencję i wykorzystując Bachtinowską estetykę „cielesnego dołu”. Właśnie w sztuce Bondy i Krejcarová odnajdywali swój azyl oraz wolność. Kluczem do odczytania poszczególnych utworów jest, moim zdaniem, transgresja – zwłaszcza ta, o której w swojej filozofii pisze Georges Bataille. Okazuje się, że „przekroczenie” stanowi dla twórców metodę wyzwolenia z okowów sztuki socrealistycznej. Lite- racki dialog prowadzony w tak zwanym samizdacie, a więc poza oficjalnym obie- giem, do dziś nie stracił swego skandalicznego wydźwięku.
Transgression as the key to reading the literary dialogue of Egon Bondy and Honza Krejcarová
Keywords: Czech literary; underground; Egon Bondy; Honza Krejcarová